2020
DOI: 10.1108/et-03-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

Implementing strategies of entrepreneurship education in Zimbabwe

Abstract: PurposeThe aim of this paper is to explore how the strategies of entrepreneurship education in clothing and textile programmes are implemented in selected Technical Colleges in Zimbabwe.Design/methodology/approachA qualitative research approach was adopted for this paper. Purposive sampling technique was used to collect data from 42 participants through in-depth interviews and focus group discussions.FindingsThe findings show that there were two principal strategies that are used by lecturers in technical coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The training aims to improve skills and learn to improve and develop attitudes, values, and experiences to be more productive. This study aligns with Mawonedzo et al (2021) that the experiential learning gained from industrial attachment is necessary for students to become future entrepreneurs in fashion design.…”
Section: Implementation Of Industrial Trainingsupporting
confidence: 84%
“…The training aims to improve skills and learn to improve and develop attitudes, values, and experiences to be more productive. This study aligns with Mawonedzo et al (2021) that the experiential learning gained from industrial attachment is necessary for students to become future entrepreneurs in fashion design.…”
Section: Implementation Of Industrial Trainingsupporting
confidence: 84%
“…The models previously identified are intended to analyze the various factors that affect individual entrepreneurial intentions (Krueger et al , 2000; Peng et al , 2013; Zhang et al , 2014). However, several social, cultural, political and economic factors influence entrepreneurial intentions in general and the creation of new companies, such as: job change, previous work experiences, quality of life, participation in certain ethnic groups, the analysis of risk capital, governmental impacts, the availability of buyers, suppliers, transportation options, qualified workforce, entrepreneurship education programmers, place of business creation, equipment and other support services (Lee et al , 2011, Liñán et al , 2011a, b; Sanchez, 2011; Bozeman and Eadens, 2020; Mawonedzo et al , 2020).…”
Section: The Entrepreneurial Intention – State Of the Artmentioning
confidence: 99%
“…There is a considerable variety of teaching approaches for entrepreneurship, including realworld examples, active learning, and student-centred learning that allows students to take a more proactive role in their development (Hodges et al, 2015;Mawonedzo et al, 2021;Yamada & Otchia, 2021). One example in this field is the Junior Enterprises, which connect theory and practice of entrepreneurship by executing projects for real clients under faculty supervision, enabling the development of not only technical skills but also soft skills, including communication, people management, problem-solving, and resource management (Mawonedzo et al, 2021).…”
Section: A Closer Look At the Competencies Of The Fashion Designermentioning
confidence: 99%
“…Another teaching strategy used in fashion programs is internships with companies, which provides students with exposure to various stages of the production process, from design to clothing production. However, research among students conducted by Mawonedzo et al (2021) revealed that internships do not necessarily expose students to entrepreneurship and management practices. As introduced in this section, the discussion proceeds to the theme of sustainability.…”
Section: A Closer Look At the Competencies Of The Fashion Designermentioning
confidence: 99%